Efficacy of repetitive transcranial magnetic stimulation on refractory epilepsy in Malaysia - Ahmad, S.B.; Lim, K.S.; Goh, H.T.; Wo, C.M.; Low, S.Y.; Tan, C.T. (ASEAN Neurological Association, 2016)
Background & Objective: Modulation of cortical excitability by low frequency repetitive transcranial magnetic stimulation (rTMS) has demonstrated therapeutic use in epilepsy. This study aimed to evaluate the efficacy of low-frequency rTMS on refractory epilepsy in a group of Malaysian subjects. Methods: Nine patients with refractory epilepsy completed the study. All patients received 10 sessions of 1Hz rTMS (1000 pulses per session) at 90% of resting motor threshold. Outcome measures included seizure frequency, Symptom Checklist-90 (SCL-90), Beck Depression Inventory II (BDI II) and Quality of Life in Epilepsy-31 (QOLIE-31). Responders were defined as having ≥ 50% seizure reduction. Results: The mean age was 33.8 years (SD 11.7), with 4 male. Three patients had mesial temporal sclerosis (MTS); 4 with focal cortical dysplasia (FCD) and two lesion-negative. Three patients achieved >50% seizure reduction at 8 weeks post-treatment, with 2 of them had improvement in the number of IED. All of the responders had FCD. The responders were younger (mean 24.7 vs. 38.3 years old), had shorter duration of illness (mean 15.7 vs. 30.5 years) and had less frequent seizure frequency prior to treatment (mean 5.5 vs. 10.8 attacks per week), as compared to the non-responders. Six patients had improvement in BDI-II scores, two in QOLIE-31 and four in SCL-90 post treatment, irrespective of seizure control. The mean scores in BDI-II improved significantly with treatment (p<0.01). Conclusion: rTMS is a potentially promising treatment for epilepsy, especially in those with FCD, younger age, shorter duration of illness and lower seizure frequency.